Rectenna circuit at 6.13 GHz to operate the sensor devices - Saxena, Anurag; K. Singh, V; ., Mohini; Bhardwaj, Sonam; Soo Chae, Gyoo; Sharma, Ashis; Kumar Bhoi, Akash (International Journal of Engineering and Technology, 2018)
There are various types of transmission through wire and wireless but wireless power transmission is the transmission of electrical energy without using any conductor or lead. At resonant frequency, 6.13 GHz wearable antenna is fabricated and tested. For making wearable an-tenna, textile material (substrate) i.e. Jeans is used for the simulation having dielectric constant 1.7. At the places where it is hard to transmit energy, wearable antenna is best suitable for this purpose, but before doing this RF is converted into DC with the help of the rectifier. Vari-ous types of graph in this paper are shown in the comparison between the power and efficiency. For simulating and design purpose of an-tenna CST, software is used. Implementation of antenna with rectifier circuit is known as rectenna and the rectenna circuit can be designed in Pspice software.Â Â